Care burden derived from the introduction of an early Lung Cancer Screening Program in high risk HIVinfected patients - Simona Cioaia; Carlos Tornero; Eugenio Sanchez; Maria Jose Alos (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2017)
We describe the care burden derived of a lung cancer screening program in HIV high risk patients. In a well selected group with the described criteria, one annual low-dose thoracic computed tomographic exploration can be applied to a 7.2% of the patients attended (95%CI 4.2-9.6), with at least one follow-up exploration in another 1.3% with the generation of at least two extra visits for explanation of the protocol and results.  If  smoking  habit  does  not  change  over  the  next  two  years,  another  4.3%  of  the  patients will  have  met  the  inclusion  criteria.  Early  detection  of  lung  cancer  with  low-dose  thoracic  computed tomographic could be of interest in HIV infected patients because the increased of risk, but would imply an increase in care burden that must be taken into account.